2020
DOI: 10.1038/s41598-020-72188-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature fluctuation on the localized pattern of action potential in cardiac tissue

Abstract: Based on the improved FitzHugh–Nagumo myocardial model driven by a constant external current, the effect of temperature fluctuation in a network of electrically coupled myocardial cells are investigated through analytical and numerical computations. Through the technique of multiple scale expansion, we successfully reduced the complex nonlinear system of equations to a more tractable and solvable nonlinear amplitude equation on which the analysis of linear stability is performed. Interestingly from this analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Indeed, the proper analysis of the spatiotemporal patterns is vital for discerning a wide range of naturally occurring and pathological phenomena. The form of the impulse propagating in the network is very relevant because it could stand as a signature to certain pathologies [24] , [25] . By selecting the appropriate electric field back 0.1 , the subsequent spatiotemporal of membrane potential is plotted in Fig.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Indeed, the proper analysis of the spatiotemporal patterns is vital for discerning a wide range of naturally occurring and pathological phenomena. The form of the impulse propagating in the network is very relevant because it could stand as a signature to certain pathologies [24] , [25] . By selecting the appropriate electric field back 0.1 , the subsequent spatiotemporal of membrane potential is plotted in Fig.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Ji et al [18] , investigated bifurcation events in intracellular calcium ions oscillations using a modified mathematical model. Takembo et al [19] , reported localized modulated wave pattern in cardiac tissue by modulational instability under thermal effect. Lan et al [20] , reported noise-induced synchronous oscillations cardiac tissue.…”
Section: Introductionmentioning
confidence: 99%